Analyzing the power quality for smart grid with hybrid conventional resources. - Kumari, Deepa; Vig, Sunny (International Journal of Engineering and Technology, 2018)
The upcoming advanced electric grid or smart grid is define as the intelligent junction of smart devices making a power system featured by the next level advancement of flow of information and electricity in two way. In this work we have come out with the better quality of energy generated at transmission side which also involves the implementation of fuzzy controller. As a goal this work is possessing working of any 2 non conventional resources i.e. wind and PV solar panel to run any non linear load by providing the controlled power to it through fuzzy controller. A general experimentation was performed to examine the current condition of art of smart grid, and removal of disturbances and their affect on power quality. Which is due to the complications, huge heterogeneity of smart grid and high amount of information to be processed, computational techniques are enabling technologies for its advancement and success in future. Hence the motive of this work is to implement fuzzy controller in combination with non conventional resources in smart grid to the production of needed amount of electricity to make the non linear load work accordingly. Different artificial technologies give support to the development of power system.Â Â